Mars's Dayside Upper Ionospheric Composition Is Affected by Magnetic Field Conditions. Issue 4 (29th April 2019) - Withers, Paul; Flynn, C. L.; Vogt, M. F.; Mayyasi, M.; Mahaffy, P.; Benna, M.; Elrod, M.; McFadden, J. P.; Dunn, P.; Liu, G.; Andersson, L.; England, S.
Abstract: Previous observations have shown that electron density and temperature in the dayside ionosphere of Mars vary between strongly and weakly magnetized regions of the planet. Here we use data from the Neutral Gas and Ion Mass Spectrometer (NGIMS) on the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft to examine whether dayside ion densities and ionospheric composition also vary. We find that O +, O 2 +, and CO 2 + densities above ∼200 km are greater in strongly magnetized regions than in weakly magnetized regions. Fractional abundances of ion species are also affected. The O + /O 2 + ratio at 300‐km altitude increases from ∼0.5 in strongly magnetized regions to ∼0.8 in weakly magnetized regions. Consequently, the plasma reservoir available for escape is fundamentally different between strongly magnetized and weakly magnetized regions. Key Points: Densities of all ion species are enhanced in strong crustal field regions Ionospheric composition above 200 km depends on magnetic field conditions The O + /O 2 + ratio is smaller in strong crustal field regions